2019
DOI: 10.29252/jech.6.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting Schools in Iran: Features and Challenges

Abstract: 1] Effect of health promoting school program in schools of the city of Babol [2] Exploring the strengths, challenges and improvement strategy for health-promoting schools from school health experts [3] Shanghai declaration: promoting health in the 2030 program of the sustainable development This article has not Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The results of studies examining the effectiveness of HPS in the food environment of Iranian schools have not been consistent [ 41 , 48 , 49 , 50 , 51 , 54 ]. Two studies, one in Urmia [ 48 ] and another in Babol [ 49 ], showed a significant increase in scores of healthy physical environment and nutrition improvement after implementing the program in schools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies examining the effectiveness of HPS in the food environment of Iranian schools have not been consistent [ 41 , 48 , 49 , 50 , 51 , 54 ]. Two studies, one in Urmia [ 48 ] and another in Babol [ 49 ], showed a significant increase in scores of healthy physical environment and nutrition improvement after implementing the program in schools.…”
Section: Resultsmentioning
confidence: 99%
“…Easy accessibility of unhealthy snacks in HPSs similar to non-HSPs is a factor that probably affected their consumption [ 25 ]. In addition, poor infrastructure and limited equipment, e.g., lack of refrigerators in canteens and sub-standard physical environments, and limited human resources (i.e., nutrition/health officer) has made the full implementation of the program almost impossible [ 42 , 54 ]. Additionally, the quick expansion of the program might have damaged the monitoring and audit mechanism(s) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, staff health is an important factor in the measurement of school health. It is plausible that since this factor has been neglected in Iran ( Charoghchian Khorasani, Peyman & Yaghobi, 2019 ) along with the strict criteria for validity testing, resulted in the omission of this important factor in the SHAT-PS. Indeed, Kaldi & Asgari ’s ( 2003 ) research indicated that the majority of primary schools’ teachers are not satisfied with their jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, given that students with a population of more than 12 million people make up a significant part of the population of Iran [ 10 ], they are affected by multiple risk factors in schools [ 11 ]. Overall, schools are one of the appropriate environments for the organization and execution of health promotion programs [ 12 ]. On the other hand, participation can be one of the basic components involved in the successful implementation of health promotion interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the PRECEDE model is a population-based epidemiological planning framework that has various ecological aspects and systematically enables planners to identify health issue features [ 22 ]. This model analyzes and describes the health problem and evaluates predisposing, reinforcing, and enabling constructs as factors affecting disease prevention and control [ 12 , 23 ].…”
Section: Introductionmentioning
confidence: 99%